2009
DOI: 10.1038/nature08123
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP intoxication of macrophages by a Mycobacterium tuberculosis adenylate cyclase

Abstract: With 8.9 million new cases and 1.7 million deaths per year, tuberculosis is a leading global killer that has not been effectively controlled. The causative agent, Mycobacterium tuberculosis, proliferates within host macrophages where it modifies both its intracellular and local tissue environment, resulting in caseous granulomas with incomplete bacterial sterilization. Although infection by various mycobacterial species produces a cyclic AMP burst within macrophages that influences cell signalling, the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
239
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(255 citation statements)
references
References 33 publications
13
239
0
3
Order By: Relevance
“…PAS inhibits Mtbdriven PGE 2 accumulation and suppresses MMP-1 secretion, suggesting that, in part, it may act as an immunomodulator to reduce tissue destruction in TB [66]. Furthermore, it has recently been demonstrated that Mtb itself produces cAMP which accesses the host cell cytoplasm to subvert the immune response [69]. One action of this pathogen-derived cAMP may be to increase MMP secretion to drive the tissue destruction that is necessary for pathogen dissemination ( fig.…”
Section: Regulation Of Mmp Expressionmentioning
confidence: 99%
“…PAS inhibits Mtbdriven PGE 2 accumulation and suppresses MMP-1 secretion, suggesting that, in part, it may act as an immunomodulator to reduce tissue destruction in TB [66]. Furthermore, it has recently been demonstrated that Mtb itself produces cAMP which accesses the host cell cytoplasm to subvert the immune response [69]. One action of this pathogen-derived cAMP may be to increase MMP secretion to drive the tissue destruction that is necessary for pathogen dissemination ( fig.…”
Section: Regulation Of Mmp Expressionmentioning
confidence: 99%
“…Consequently, intracellular cAMP concentrations in mycobacterial cells are considered to be~100-fold higher than those of other bacteria (Dass et al, 2008;Padh & Venkitasubramanian, 1976, 1980, but the significance of this is not known. Secretion of cAMP directly into host macrophages after infection has been reported and is thought to be important in tuberculosis pathogenesis (Agarwal et al, 2009;Bai et al, 2009;Lowrie et al, 1975). M. tuberculosis H37Rv contains a single CRP-FNR homologue encoded by the gene Rv3676 (Cole et al, 1998), which is 32 % identical to the E. coli CRP over 189 amino acid residues.…”
Section: Introductionmentioning
confidence: 99%
“…Mycobacterium smegmatis) mycobacteria (2,3). Recent evidence has highlighted the importance of cAMP in modulating the host macrophage response to M. tuberculosis infection (4). A single adenylyl cyclase was shown to be responsible for the burst of cAMP that is seen in the macrophage following phagocytosis of M. tuberculosis, and this bacterially derived increase in cAMP was essential to attenuate the response of the macrophage to the pathogen.…”
mentioning
confidence: 99%
“…Instead, we identified a Class III phosphodiesterase, the product of the rv0805 gene (accession NP_215320), that was capable of degrading mycobacterial cAMP (6). Indeed, overexpression of Rv0805 was used to reduce intracellular levels of cAMP in M. tuberculosis to show that bacterially derived cAMP was essential to attenuate macrophage killing (4). Rv0805 is a member of the superfamily of metallophosphoesterases (MPEs) 6 that has been well characterized biochemically and structurally (7)(8)(9).…”
mentioning
confidence: 99%